An enzyme‐linked immunosorbent assay and reference ranges for bisphosphoglycerate mutase in human erythrocytes - Takubo, Takayuki (J Clin Lab Anal, 1998)
We established an enzyme‐linked immunosorbent assay (ELISA) system for the determination of human bisphosphoglycerate mutase (BPGM) protein content in human erythrocytes using a polyclonal anti‐BPGM antibody, we determined reference ranges for BPGM protein content, synthase activity, and specific activity in human erythrocytes. We produced a recombinant human BPGM (rBPGM) by gene manipulation using E. coli and then obtained the polyclonal antibody by immunizing rabbits with purified rBPGM. The reproducibility of the ELISA was in an acceptable range with a coefficient of variation under 1.5%. The ELISA was reliable in the range of 0.1 to 10 ng/mL. The polyclonal anti‐rBPGM antibody did not show any cross‐reaction with recombinant human B type phosphoglycerate mutase, which is highly homologous to rBPGM. The ELISA was found to be practical for the determination of BPGM protein content in human erythrocytes. The mean BPGM protein content was 56.3 ± 9.7 μg/mL in whole blood (mean ± SD, n = 50). The ELISA can be used to examine various hematologic disorders with abnormal red cell size and cell counts, and to detect BPGM enzymopathy in human erythrocytes. J. Clin. Lab. Anal. 12:263–267, 1998. © 1998 Wiley‐Liss, Inc.